INFLUENCE OF THE POLICY OF NON-TARIFF BARRIER IN EUROPEAN UNION ON EXPORT OF INDONESIAN COCOA BEANS IN 2011 - Shinta, Clara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research discusses about â€œInfluence of The Policy of Non-Tariff Barrier in European Union on Export Of Indonesian Cocoa Bean in 2011â€. The purpose is this research is to find out how is the influence of the policy of non tariff barrier in European Union on export of Indonesian cocoa beans in 2011. Cocoa beans is a leading commodity where Indonesia is a producer country thirdly after Ivory Coast and Ghana. In 2011, the deacreased in export value of Indonesian cocoa beans to the European Union fell from US$ 55 million to US$ 4 million. This is due to the policy of non-tariff barrier of European Union which obliges fermentation requirement at Indonesian cocoa beans. Most Indonesian farmers ignore the post-processing stages of cocoa beans.This is qualitative research which used descriptive explanative methods, and collecting datas from books, journals, articles, mass media, official publications and relevant websites. This paper used the mercantilism perspective, analysis unit group countries written by Mohtar Masâ€™oed and the theory is International Trade.The result of the research is the development of export value of cocoa beans Indonesia has decreased in 2011. The main cause is the existence of fermentation requirements (non tariff barrier) in the European Union market which is the most important stage in the processing of chocolate. Ivory Coast and Ghana are the good cocoa beans producers in European Union due to the quality of the fermented beans. The policy relating to quality of cocoa beans are discussed in Regulation (EC) No. 178/2002. This regulation discusses about the European Food Safety Authority and laying down procedures in matters of food safety.Keywords : Non Tariff Barrier, Regulation (EC) No. 178/2002, International Trade, Mercantilism Perspective